(untitled) - Kolker, Robert Phillip (Boston, 2006)
This text looks at film from part to whole--from the shot and the cut to the cultural, political, and economic contexts in which films are made. "Teaching Film is about getting control of the image and handing that control over to students," argues author Robert Kolker, and that's just what he does in his teaching and writing about film, including in this outstanding textbook and DVD-ROM package.
Keywords: Motion pictures,Culture in motion pictures,Hình ảnh động,Văn hóa trong phim